Production Chains: A Difficult Research Agenda - Bose, A. J. C.; Sinha, Saroj (Prabandhan: Indian Journal of Management, 2012)
After introducing the concept of the production chain, the paper examines the empirical findings about it in the global automobile industry. On this basis, a simple and yet exciting research problem about organizational capabilities in value creation is derived with its associated research questions. The paper then points out the difficulties the authors encountered in executing this research project, even as it still remains a worthwhile research quest to unravel how modern industrial firms create value by their choice of the nature and content of subcontracting and human resource practices.